Analisis Representasi Generasi Sandwich Dan Nilai Pendidikan Moral Dalam Film Home Sweet Loan: Kajian Teks Kultural Clifford Geertz - Sylvania Lucky Bahar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the representation of the sandwich generation in the Indonesian film Home Sweet Loan as a reflection of contemporary socio-economic realities faced by young adults. The film portrays individuals who are simultaneously responsible for supporting their parents and financing their own future, creating complex moral, emotional, and financial pressures. Using a qualitative interpretative approach, this research applies Clifford Geertz’s theory of symbolic interpretation to analyze meanings embedded in visual narratives, dialogues, and character interactions. Data were collected through repeated viewing of the film, scene documentation, and thematic categorization based on moral responsibility, family obligation, and economic struggle. The findings indicate that Home Sweet Loan constructs the sandwich generation as morally resilient yet vulnerable, highlighting internal conflicts between personal aspirations and familial duties. The film also emphasizes the role of cultural values in shaping perceptions of responsibility and sacrifice. This study contributes to film and cultural studies by demonstrating how cinema functions as a medium for social reflection and moral education. The results are expected to enrich academic discussions on Indonesian cinema and the lived experiences of the sandwich generation.